Marketing justification of a project focused on introducing the innovative cloud service “MedKid” to the market; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Selevich O. S. Olga Semenovna (2016, 2016)
Title screen